Densitas tulang mandibula pengguna obat anti hipertensi calcium channel blocker (CCB) melalui radiograf panoramik - Gunawan Gunawan; Suhardjo Sitam; Lusi Epsilawati (Ikatan Radiologi Kedokteran Gigi Indonesia, 2020)
Objectives: The purpose of this research was to describe radiographic density of mandibular bone in calcium channel blocker anti-hypertensive drug users. Bone density in the mandible is assessed from the trabecular. Panoramic radiograph is a routine examination that is often done in dentistry that can be used to assess changes in quality in the form of changes in bone density in users of anti-hypertensive calcium channel blockers Material and Methods: This research is a descriptive study of 21 panoramic radiographs of calcium channel blocker anti-hypertensive drug users aged 40-75 years. Panoramic radiograph archive density checks in the distal region of the foramen mentale and the mandibular angular region using software image j, with the final result was the percentage between bone and marrow. Results: This research showed the average radiographic density in male using calcium channel blocker antihypertensive drugs was 18.81% and the average radiographic density in female was 20.92%. Conclusion: Based on the results of the study found that the average radiographic density of female patients taking antihypertensive drugs calcium channel blockers was higher than male.